2021
DOI: 10.1021/acsaem.1c02738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pristine Graphene on Methylammonium Lead Iodide Films and Implications on Solar Cell Performance

Abstract: The relatively low stability of solar cells based on hybrid halide perovskites is the main issue to be solved for the implementation in real life of these extraordinary materials. Degradation is accelerated by temperature, moisture, oxygen, and light and mediated by halide easy hopping. The approach here is to incorporate pristine graphene, which is hydrophobic and impermeable to gases and likely limits ionic diffusion while maintaining adequate electronic conductivity. Low concentrations of few-layer graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Previous studies have reported that a lower concentration of graphene may lower the activation energy. 42 However, in our composite system, the concentration of graphene is too low that it may have minimal effect on the activation energy. Figure 7e shows a schematic arrangement of filament formation by the bromide vacancies (V Br ).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies have reported that a lower concentration of graphene may lower the activation energy. 42 However, in our composite system, the concentration of graphene is too low that it may have minimal effect on the activation energy. Figure 7e shows a schematic arrangement of filament formation by the bromide vacancies (V Br ).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…The increase in resistivity with temperature is just opposite nature of semiconductor. 42 This implies the role of graphene in the composite system as a conductive medium, due to which a small increase in resistivity is observed in the D2 device. Furthermore, the Schottky barrier is also reduced during the voltage bias to boost the charge injection through the ITO/g-FAPbBr 3 interface.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, a small concentration of graphene platelet (G‐platelet) was also incorporated in the active layer of a solar cell to study its effect on structural, optical properties, and device performance. [ 158 ] The impermeable nature to gases and hydrophobic nature of graphene sealed the surface of grains resulting in low ionic diffusion. In addition, the presence of graphene enlarged the crystalline domain along with its high preferential orientation, and increased the porosity of films and photovoltaic parameters.…”
Section: Roles Of Graphene and Its Derivativesmentioning
confidence: 99%
“…Graphene is a material with high potential applications [1][2][3]. These applications include solar cells [1], LEDs [2], and many other applications [3]. The same is true for graphene oxide [4].…”
Section: Introductionmentioning
confidence: 99%